The political in contemporaneity: Approaches from the psychopolitics of Byung-Chul Han. - Ullauri Betancourt, Santiago Andrés; Rivas Plata, Anthony Medina; Cáceres Silva, Andrea Vanessa (Ius Humani. Jornal do direito, 2024)
The notion of the political in the contemporary era has developed a new paradigm characterized by structured individualism under psychic control and self-exploitation. In this context, Byung-Chul Han argues that, under the neoliberal system, power no longer operates through physical discipline or external coercion, but through psychological manipulation. The individual is transformed into an " entrepreneur of the self," reducing negativity to a strictly inert framework, leading to a more subtle form of domination in which the individual internalizes the logic of performance and constant optimization. In this way, psychopolitics acts silently on the mind and emotions, fostering a self-exploitation in which personal success and productivity become imperatives. For Han, this logic not only depoliticizes the individual, but also eliminates his or her capacity for resistance, where conflict, which in classical theories of the political is essential, disappears in favor of a society that fosters individual competition and digital surveillance. In the face of this, Han explores the need to reconstruct the political, seeking spaces that revitalize political action through critical questioning.